Understanding gender dynamics for change in smallholder pig value chain development - Ouma, Emily A. (International Livestock Research Institute, 2016)
The pig sector is developing rapidly in Uganda, opening opportunities for smallholders to tap into this developing value chain. The researchers conducted a pig value-chain analysis and identified constraints and opportunities.